Answer:
Step-by-step explanation: Sub -3 into where all the u’s are. So it would be
(-3)^2 - 2(-3) + 4
Which would equal 19
Answer:
Explanation:
We have:
(
2
x
+
3
)
(
4
x
2
−
5
x
+
6
)
Now let's distribute this piece by piece:
(
2
x
)
(
4
x
2
)
=
8
x
3
(
2
x
)
(
−
5
x
)
=
−
10
x
2
(
2
x
)
(
6
)
=
12
x
(
3
)
(
4
x
2
)
=
12
x
2
(
3
)
(
−
5
x
)
=
−
15
x
(
3
)
(
6
)
=
18
And now we add them all up (I'm going to group terms in the adding):
8
x
3
−
10
x
2
+
12
x
2
+
12
x
−
15
x
+
18
And now simplify:
8
x
3
+
2
x
2
−
3
x
+
18Step-by-step explanation:
The answer is the first option: it has the same domain as the function f(x) = - √(-x).
The domain is the set of x-values for which the function is defined.
The square root function is defined only for zero and positve values.
- x is positive when x negative.
So the domain for - √(-x) and √(-x) are the same: x less than or equal to zero.